Asosiasi Auto-Immune Bullous Disease dengan Interstitial Pneumonia - El Farah, Prajnamita Manindhya; Hasyyati, Enggar Yusrina; Hasanah, Caprisia Tiaravicka; Khoirunnisa, Inas (Cermin Dunia Kedokteran, 2024)
Numerous inflammatory, neoplastic, and genetic skin disorders are associated with interstitial lung disease (ILD), a fibrosing inflammation of lung parenchyma with significant morbidity and mortality. There is inconsistent data regarding the association between bullous pemphigoid and pneumonia. This article details the clinical manifestations of bullous pemphigoid (BP) and pemphigus vulgaris (PV) associated with interstitial pneumonia, specific diagnostic strategies, underlying mechanistic connections, and possible treatments.